Football and Manliness : An Unauthorized Feminist Account of the NFL - Oates, Thomas Patrick (Book collections on Project MUSE., 2017)
"Professional football is often parodied as a simplistic, straightforward assertion of male power. However, in this book Thomas P. Oates examines the shifting presentation of masculinity and race through media coverage of professional football and contends that in contemporary US media culture, the NFL offers more than entertainment: it provides a space where the anxieties and contradictions characterizing the dominant formations of contemporary masculinity can be worked through, adjusted, and recalibrated to meet contemporary challenges. Guided by feminist theory, Oates argues that during a period of intense political, cultural, and economic change, mediated professional football (through a variety of media forms), NFL entertainments are subtly adjusting dominant forms of masculinity, aligning them with the demands of a new economy reality and the shifting relations of race, class, gender, and sexuality. Ultimately, the book brings sustained critical feminist attention to one of the most profitable, culturally powerful, and recognizable branded media products in the contemporary US. It aims to map some important ways racialized masculinity is positioned, adjusted, and deployed in a changing cultural and economic climate, and to identify possible spaces for resistance"--